School is a place for everyone! - Alves, Maria Alda de Sousa (2022)
The summary makes public reflections on inclusive education through the film Forget Me Not. It is a documentary that tells the story of Emilio, three years old, who was born with Down’s Syndrome and is preparing to enter public school in New York City. The educational system of this city follows a segregating model, leading Emílio's family to have experiences of struggle for an inclusive school. The documentary invites us to be strange and to change paradigms in the life history of people with intellectual disabilities regarding accessibility and permanence in educational institutions. Scientific research finds that environments that value difference benefit students with and without disabilities. Among children with Down’s syndrome, there is evidence that the amount of time spent with peers without disabilities is associated with better memory, language skills, and literacy.